EVALUATING PERFORMANCE TO IMPROVE CONTAINER THROUGHPUT AND BUSINESS STRATEGIC DECISION FOR NILAM MULTIPURPOSE TERMINAL PORT OF TANJUNG PERAK (The Indonesian Journal of Business Administration, 2019)
The purpose of this study is to to find the root cause of not optimal (stagnant) performance that aims to increase throughput optimally and the right business strategy for the future of Nilam Multipurpose Terminals by using Fishbone Analysis, External & Internal Analysis, and SWOT analysis. Based on the exploration it can be concluded that the high Vessel Turnover Time that occurs in Nilam Multipurpose Terminal is a cause that should be evaluated and optimized so that it can increase throughput in the future. Based on Fishbone Analysis result, it can be seen that there are several factors that cause the high vessel turnover time. External Analysis (PEST Analysis) and Internal Analysis (Core Competencies) are input for SWOT Analysis. From the problem scoring, the problem that become the core for increasing container throughput of Nilam Multipurpose Terminal is high vessel turnover time. Several alternative solutions from the results of brainstorming are joint agreement, workshop & HR training, optimize talent pool management, pilot clusterization, upgrade facility and maintenance evaluation.From mapping of alternative solutions and quantitative comparison matrix, the result show that solution that can be done in the near future and have a significant impact to increase container throughput of Nilam Multipurpose Terminal is execute workshop and training (in-house and/or ex-house) to improve and evaluate the capabilities and skills of human resources serving in Nilam Multipurpose Terminal and Port Operation Command Center (POCC) team. An activity plan has been prepared for the implementation plan of the solution.Keywords:  performance, throughput, fishbone analysis, external & internal analysis, SWOT analysis.